Coaching & mentoring - MacLeod, Leo; Brounstein, Marty (--For dummies., 2023)
Coaching & Mentoring For Dummies is the playbook to help supervisors change their role from doer/manager to coach/mentor. Leadership and coaching expert Leo MacLeod, shares the secrets of motivating employees to find purpose in their work and grow as independent problem solvers—without micromanaging them. Written for today’s changing workplace, the book provides guidance on leading diverse teams, working with younger generations and working remotely. Business is built on relationships, especially in today’s global economy. Coaching and mentoring are more important than ever. This readable guide provides you with the skills to strengthen connections and pass on useful knowledge that will help teams elevate their productivity and quality of work.